2001
DOI: 10.1053/jhep.2001.22652
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intrahepatic metastasis of human hepatocellular carcinoma by Rho-associated protein kinase inhibitor Y-27632

Abstract: Hepatocellular carcinoma (HCC) is one of the most common tumors worldwide, and is currently the third-leading cause of cancer death among males in Japan. 1 The high incidence of recurrence is the most crucial prognostic factor for patients with HCC. 2 Through a combination of pathologic and genetic approaches, recurrence of HCC has been divided into 2 types: multicentric occurrence of new tumors 3-5 and intrahepatic metastasis of the original HCC. Several clinicopathologic studies have shown that the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 16 publications
(28 reference statements)
6
85
1
Order By: Relevance
“…The results of the present study revealed that afzelin inhibited the protein expression levels of MRCKα and ROCK1, clarifying that downregulation of LIMK1 by afzelin is due to its inhibitory effect on MRCKα and ROCK1, upstream in its signaling pathway. Previous studies have demonstrated that ROCK inhibitors appear to reduce the invasive ability of tumor cells in vitro and prevent the dissemination of tumor cells in vivo in different types of cancer, particularly in prostate cancer (10,(13)(14)(15)(16)(17)38). Furthermore, LIMK1, MRCKα and ROCK1 are proteins of interest in the development of novel cancer therapies due to their involvement in regulating actin organization (7) and, in combination with other proteins, maintaining the tight regulation of normal cell growth and differentiation (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study revealed that afzelin inhibited the protein expression levels of MRCKα and ROCK1, clarifying that downregulation of LIMK1 by afzelin is due to its inhibitory effect on MRCKα and ROCK1, upstream in its signaling pathway. Previous studies have demonstrated that ROCK inhibitors appear to reduce the invasive ability of tumor cells in vitro and prevent the dissemination of tumor cells in vivo in different types of cancer, particularly in prostate cancer (10,(13)(14)(15)(16)(17)38). Furthermore, LIMK1, MRCKα and ROCK1 are proteins of interest in the development of novel cancer therapies due to their involvement in regulating actin organization (7) and, in combination with other proteins, maintaining the tight regulation of normal cell growth and differentiation (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The Rho GTPase myotonic dystrophy kinase-related Cdc42-binding kinase α (MRCKα), Rho-associated coiled-coil containing protein kinase (ROCK)1 and ROCK2 are responsible for the activation of LIMK1 (9,12). Previous studies have demonstrated the ability of ROCK inhibitors to reduce the invasive ability of tumor cells in vitro and prevent the spread of tumor cells in vivo, including melanoma and fibrosarcoma cells, as well as liver, breast, lung and prostate cancer tumor cells (13)(14)(15)(16)(17) Thus, inhibitors of LIMK1, MRCKα and ROCK1/2 are considered to restore normal cell proliferation and provide a key strategy for cancer treatment (18). Therefore, the aim of the present study was to evaluate the in vitro anti-prostate cancer activity of afzelin and its effect on prostate cancer-associated kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Along with its partner protein Max, c-Myc regulates an estimated 10% to 15% of genes in the human genome, and globally reprograms cells and drives proliferation (1)(2)(3). Aberrant regulation and overexpression of c-Myc are observed in most tumor types, and the c-Myc signaling is believed to play a critical role in oncogenesis (4)(5)(6)(7). A large body of studies have shown that c-Myc is pathologically amplified and/or overexpressed in breast cancers (8,9), particularly in late-stage tumors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The link between transcription with transformation, cell invasion, and metastasis is particularly interesting. Ever since it was shown that overexpression of either RhoA, Rac1, or Cdc42 transforms and promotes the metastatic phenotype of cultured 3T3 fibroblasts (Ballestero et al, 1991;Perona et al, 1993;del Peso et al, 1997), many studies have described the physiological relevance of Rho signaling and overexpression in human tumors (Clark et al, 2000;Mira et al, 2000;Van Golen et al, 2000a,b;Abraham et al, 2001;Kamai et al, 2001;Keely, 2001;Matsumoto et al, 2001;Takamura et al, 2001;Takemoto et al, 2001). Overexpression of Rho GTPases occurs in many types of human tumors, and RhoA and Rac2 constitute early markers for tumor progression of head and neck squamous cell cancer (Abraham et al, 2001).…”
Section: Introductionmentioning
confidence: 99%